Impact of Cotton Preparation on Grade and Price - Ee Abdel mageeed, Gaafer; Y. Abusalma, Abas; S.Fadllala, Ahmed; M,Gaafer, Atif (Gezira Journal of Engineering and Applied Sciences, 2021)
This study is concerned with enhancement of the quality and grade of Sudanese cottons in order to improve their marketability in international markets. Field experiments were conducted during 2()()0 2002 at Gezira Scheme, Sudan on Barac (67)B variety in Baracat Block , while the variety Barakat-90 was the subject of the study in Umdagatsi Block. The objectives of this study were to improve cotton fibre quality, grade and to reduce honey due contamination in the commercial cotton cultivars; and Barac(67)B Results indicated that scheduled cotton picking and seed cotton cleaning improved cotton quality by a full grade. Also, cotton homogeneity was improved ensuing lower fiber properties variability and reduced stickiness contamination. The results of this study ascertained that on amount of 21.2 million dollars could be secured to the national income and Sudan's cotton position in the international marked is strengthened, provided that recommendation of this study, are applied.